PERLINDUNGAN NASABAH DIBIDANG PERDAGANGAN BERJANGKA KOMODITI DALAM PENERIMAAN NASABAH SECARA ELEKTRONIK ON-LINE - Fadly Khairuzzadhi (2021)
Futures trading can be an alternative funding for the development of the economic sector in the context of national development and also serves as a means of investment for customers, both government and foreign or local private parties to develop their investment. Investing activities are of course inseparable from risk, because in every investment there is always a large amount of risk that is directly proportional to ROI (Return Of Investments) or income. To minimize this risk, the two parties enter into a cooperation agreement between the customer and the brokerage company in which the customer owns the capital and the brokerage company acts as a facilitator. Commodity Futures Trading is regulated in Law No. 10 of 2011. In the process, customers can join online registration fillers, but along the way there are still various obstacles in filling out online registration because customers do not meet with the futures broker to get an explanation. clear regarding risks and transaction mechanisms. And also the long dispute settlement process in accordance with Bappebti Regulation No. 4 of 2020 concerning Guidelines for Settlement of Customer Disputes in the Commodity Futures Trading Sector.